BLESSING THAT FLOWS: A CONCEPTUAL METAPHOR ANALYSIS OF BLESSINGS IN ENGLISH AND INDONESIAN - Akhida Cahya Lestari; Anandya Asprillia; Ahmad Zaidi (Ma Chung Press, 2026)
This study looks at how people talk about blessings, using the lens of cognitive semantics and focusing on metaphors in religious language. The main goal is to pinpoint the key conceptual metaphors behind words related to “blessing,” and to show how these metaphors shape meaning in real contexts. To do this, data from religious texts and contemporary written sources in both Indonesian and English were gathered. Then, using qualitative descriptive methods and conceptual metaphor theory, we sorted out the metaphorical expressions, identified their source and target domains, and checked how often they popped up in different themes. The findings stand out: people often describe blessings using metaphors like wealth, abundance, journey, light, and divine gift. But the most common are BLESSING IS WEALTH and BLESSING IS ABUNDANCE, which tie spiritual value tightly to ideas of material gain or measurable benefit. The patterns aren’t just decorative language; they're fundamental frameworks that guide how believers think and talk about religious concepts. In short, the research shows that metaphor isn’t just fancy phrasing in religious language—it’s central to how people make sense of spiritual ideas, revealing deep, culturally rooted ways of seeing the world.